(untitled) (EAAE Annual Conference Proceedings, 2019)
The Faculty of Architecture at the University of Porto (FAUP), founded in 1979, and benefiting from the legacy of the School of Fine Arts (ESBAP), is internationally recognized and a worldwide reference in architectural teaching. Important names of the ‘School of Porto’ studied and lectured at ESBAP and FAUP. Fernando Távora (1923–2005), Álvaro Siza (b. 1933) and Eduardo Souto de Moura (b. 1952) — the last two Pritzker Prize winners, among many other distinctions — might be considered the three pillars of the school, although their contribution cannot be considered without their predecessors, the group of people they worked with and the Portuguese particular context.